Action research as a teaching armoury for the language teacher - David, M.K.; Kuang, C.H. (2016)
Given the easy availability of information due to social media, language teachers need to move beyond their role as mere disseminators of information to that of as an innovator, enabling learners to think critically. To do so, language teachers must make action research an indispensable part of their language teaching armoury. They must realise that the challenges of teaching, be it student disinterest, poor comprehension skills or weak performances can be tackled. One way of doing so is to conduct some research within their own classrooms so as to seek solutions to overcome these challenges. This paper highlights the importance of action research and how it can be conducted. Using two case studies as examples, this paper hopes that these experiences in action research will encourage teachers to conduct their own classroom research in overcoming any issue they face in their respective language classrooms. It is also hoped that this recommendation can enable teachers move beyond their traditional roles of merely providing information to students to creating greater learning opportunities and experience in class. Last but not least, this paper aims to motivate teachers to further enhance themselves in facing the current challenges of language teaching.